The Relationship between Malnutrition and Subjective Taste Change Experienced by Patients with Cancer Receiving Outpatient Chemotherapy Treatment - KOLAÇ, NURCAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Taste changes and malnutrition are two important problems in patients with different types of cancer. This study was conducted to evaluate the relationship between malnutrition and subjective taste changes experienced by cancer patients receiving outpatient chemotherapy. The study used a cross-sectional design and was carried out with 1382 patients with cancer receiving outpatient chemotherapy. Of the patients, 63.1% experienced taste changes. It was determined that 8.8% of patients had malnutrition according to the Mini Nutritional Assessment. The mean scores of patients experiencing malnutrition and being at risk for malnutrition from all sub-dimensions of The Chemotherapy-induced Taste Alteration Scale (CiTAS) were found to be higher than the patient group evaluated to have normal nutrition. It was determined that a unit increase in the scores of the parageusia and phantogeusia subscales of the CiTAS increased the risk of malnutrition by 3.36 times (%95 CI= 2.68-4.02). In line with these results, we recommend that patients with cancer receiving chemotherapy should be routinely evaluated in terms of taste changes in clinical practice and that they should be followed up in terms of malnutrition in the presence of taste changes.
Keywords: SMELL ALTERATIONS; BREAST; PREVALENCE; PERCEPTION; DISORDERS; SEVERITY; DISEASE; IMPACT